Modulation of expression of Programmed Death-1 by administration of probiotic Dahi in DMH-induced colorectal carcinogenesis in rats - Mohania, Dheeraj; Kansal, Vinod K.; Kumar, Manoj; Nagpal, Ravinder; Yamashiro, Yuichiro; Marotta, Francesco (Acta Biomedica Atenei Parmensis, 2013)
Interaction of probiotic bacteria with the host immune system elicits beneficial immune modulating effects. Although, there are many published studies on interaction of probiotics with immune system focusing on activation of immune system by bacterial cell wall through the engagement of Toll-like receptor family; very few studies have focused on molecules involved in the T-cell activation, and not much work has been executed to study the correlation of probiotics and programmed death-1 in colorectal carcinogenesis in animal models. Hence, the present study was carried out to assess the effect of probiotic Dahi on expression of programmed death (PD-1) in colorectum of 1, 2-dimethylhydrazine treated Wistar rats. Methods: DMH was injected subcutaneously at the rate of 40 mg/kg body weight per animal twice a week for 2 weeks. A total of 168 male Wistar rats were randomly allocated to seven groups, each group having twenty-four animals. The rats were euthanized at the 8th, 16th and 32nd week of the experiment and examined for the expression of PD-1 in colorectal tissues by immunohistochemical staining. Results: Expression of PD-1 was observed in colorectal tissues of normal and DMH-treated rats. Feeding rats with probiotic Dahi or the treatment with piroxicam decreased the expression of PD-1 in DMH-induced colorectal mucosa, and the combined treatment with probiotic Dahi and piroxicam was significantly more effective in reducing the expression of PD-1. Conclusion: PD-1 expressed independent of carcinogen administration in normal colonic mucosa and may play a role in modulation of immune response in DMH-induced colorectal carcinogenesis. The present study suggests that probiotic Dahi can be used as an effective chemopreventive agent in the management of colorectal cancer